Historicidad y carnalidad; invisibilidad de la psicosomática - Márquez Araiza, Erick Felipe (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
The revolution of the space concepts, matter and time at the beginning of the XX century it is without a doubt an important referent in our way of understanding the reality. But him I call an important referent because it is not the only form of understanding the reality in general as the properly human, such one it is the discussion that Einstein and Bergson sustain, according to the narration of Merleau-Ponty, on the impact and reach of such concepts built by the physics in the man's understanding. One can think that thanks to the sharpness of the theory of the relativity has concluded everything to say about the since time already anything is it necessary to say in the face of the precision of such a theory? The importance of such a discussion is not smaller, because it shows us the necessity to prevent that a speech sutures other discursivities, already that the truth is not a neither one can obtain for an only road. This same restlessness is the one that motivates the present thesis when discussing the phenomenon of the psychosomatic, thematic that acquires popularity and interest in the psychiatry and in the psychology. The title of the present work: Historicity and carnalidad; the invisible of the phenomenon psychosomatic, it seeks to reflect the escotomización of two key concepts in the theory psychosomatic specifically the one developed by Pierre Marty 1. I use the concept of escotomizar to refer the blind points of this theory; hence I don't seek demeritarla since in their clinical dimension he/she has had important achievements, but if to show the impossibility that a speech can tell everything; because all speech leaves of a point of view, it uses certain suppositions with which it builds this point of view and it is the work of this thesis to analyze all these suppositions.

La revolución de los conceptos de espacio, materia y tiempo a principios del siglo XX es sin duda un referente importante en nuestra manera de comprender la realidad. Pero lo llamo un referente importante porque no es la única forma de entender la realidad en general como la propiamente humana, tal es la discusión que Einstein y Bergson sostienen, según la narración de Merleau-Ponty, sobre el impacto y alcance de tales conceptos construidos por la física en la comprensión del hombre. ¿Se puede pensar que gracias a la agudeza de la teoría de la relatividad ha concluido todo decir sobre el tiempo pues ya nada hay que decir ante la precisión de tal teoría? La importancia de tal discusión no es menor, pues nos muestra la necesidad de impedir que un discurso suture otras discursividades, ya que la verdad no es una ni se puede obtener por un único camino. Esta misma inquietud es la que motiva la presente tesis al discutir el fenómeno de la psicosomática, temática que adquiere popularidad e interés en la psiquiatría y en la psicología. El título del presente trabajo: Historicidad y carnalidad; lo invisible del fenómeno psicosomático, pretende reflejar la escotomización de dos conceptos claves en la teoría psicosomática específicamente la desarrollada por Pierre Marty 1. Utilizo el concepto de escotomizar para referir los puntos ciegos de dicha teoría; no por ello pretendo demeritarla ya que en su dimensión clínica ha tenido logros importantes, pero si mostrar la imposibilidad de que un discurso pueda decirlo todo; pues todo discurso parte de un punto de vista, utiliza ciertos supuestos con los cuales construye dicho punto de vista y es la labor de esta tesis analizar todos estos supuestos.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2012-0048; Psicosomática; Ciencia; Moderna; Cuerpo; Psicoanálisis; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/78